PENGARUH KUAT TEKAN DAN KUAT GESER SAMPEL DRYSIDE OF OPTIMUM (KERING OPTIMUM) DAN WETSIDE OF OPTIMUM (BASAH OPTIMUM) PADA TANAH LEMPUNG - Lumeilia Afriani; Iswan Iswan; Armen Febri (UNIVERSITAS LAMPUNG, 2015)
Clay is a type of soil with low bearing capacity, the water is very large influence on the physical and mechanical behavior. Clay in the dry state optimum swell properties that are larger than the current optimum wet clay compacted. This is because at the time of clay in the dry state of opti - mum relative shortage of water so that the clay has a greater ability to absorb water. In experi - ments clay in dry conditions and wet optimum optimum useful to know the carrying capacity of the soil in dry and wet conditions. From the results of research conducted generate free compressive strength value (qu) and the value of cohesion (c) and the maximum shear strength soil in wet conditions the optimum moisture content, dry optimum and optimum. In optimum conditions produce the highest value for the com- pressive strength of free, direct shear strength and cohesion values. This is because the optimum conditions the maximum soil density, so that the soil is not easily mengemang. In dry conditions the optimum clay soil density unstable, so that the grains of soil are not mutually binding, whereas in wet conditions the optimum pressure on the grains of soil is very high, so that the soil has a high plasticity.